2018
DOI: 10.1002/ece3.3981
|View full text |Cite
|
Sign up to set email alerts
|

Diel movement of brown trout,Salmo trutta, is reduced in dense populations with high site fidelity

Abstract: The movement of individuals within preferred areas is reduced by a high availability of food and information about its distribution, while high number of competitors promotes increased movement. Experienced animals use information about social and physical environment to improve resources exploitation, tended to maintain positions within the preferred areas and reuse the environment that is often referred to as site fidelity. In this study, radio‐telemetry was used to observe the movements of 98 adult brown tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 113 publications
(166 reference statements)
1
4
0
Order By: Relevance
“…In central Europe, burbot display mostly nocturnal activity (Müller 1978, Eick 2013) that peaks after dusk and subsequently decreases (Slavík et al 2005), which corresponds with our results during the whole spawning season. Specimens from both groups (wild and farmed) were distributed within a few kilometers long stretch along the longitudinal profile of the river, which is typical for fish migrations in headwaters (Northcote 2010) and consistent with the findings of earlier studies of salmonids in the study area (Slavík et al 2012(Slavík et al , 2018. Farmed burbot displayed higher movement activity during the expected spawning peak than their wild conspecifics, which agrees with the general assumption of higher investment in movement and a less successful spawning process in farmed fish.…”
Section: Movement Activitysupporting
confidence: 87%
See 1 more Smart Citation
“…In central Europe, burbot display mostly nocturnal activity (Müller 1978, Eick 2013) that peaks after dusk and subsequently decreases (Slavík et al 2005), which corresponds with our results during the whole spawning season. Specimens from both groups (wild and farmed) were distributed within a few kilometers long stretch along the longitudinal profile of the river, which is typical for fish migrations in headwaters (Northcote 2010) and consistent with the findings of earlier studies of salmonids in the study area (Slavík et al 2012(Slavík et al , 2018. Farmed burbot displayed higher movement activity during the expected spawning peak than their wild conspecifics, which agrees with the general assumption of higher investment in movement and a less successful spawning process in farmed fish.…”
Section: Movement Activitysupporting
confidence: 87%
“…Different spatial distributions of farmed burbot throughout the spawning season, including during the expected spawning peak, suggested a lower association of both sexes for farmed compared to wild fish. Telemetry methods are useful techniques with a potential to provide interesting data about the mutual spatial distribution of tagged individuals in natural conditions (Slavík et al 2007(Slavík et al , 2018. However, obtained results should be interpreted as an indicative measure of social contacts within observed populations in the wild, as there can also be other non-tagged individuals present.…”
Section: Distances Between Individualsmentioning
confidence: 99%
“…In fish species, such as three-spined stickleback ( Gasterosteus aculeatus ) have been observed variances in personal traits including boldness and aggressivity, affecting social bonding and other interindividual relationships ( 206 ). As we and others observed, the personal traits of social fish individuals origin in genetics, interindividual relationships and interspecies relationships or environmental factors during the early life as well as during the adulthood ( 206 210 ).…”
Section: Face Validity Of Rodent and Zebrafish Modelsmentioning
confidence: 60%
“…Contrary to our results, previous studies observed riverine and lacustrine brook trout being most active during the day or having activity evenly dispersed throughout the day and night (Allan, 1981; Cote et al, 2020; Larranaga et al, 2019). Daily activity of salmonids can be influenced by density, drift of aquatic insects and presence of other salmonid species (Railsback et al, 2005; Slavík et al, 2018; Larranaga et al, 2019). Our findings using PIT antenna detections suggest brook trout diel movements were dependent on environmental conditions in the LPR.…”
Section: Discussionmentioning
confidence: 99%